Efficiency of Malaysian stock market: a revisit based on analysts’ recommendations - Ling, Pick Soon; Ruzita Abdul-Rahim, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
A market is efficient in the weak form when current prices reflect past market information (prices and volumes) in such that a technical analysis is no longer a viable tool for generating abnormal returns. This study re-investigated the weak form efficiency of Malaysia stock market using technical trading strategies. To ensure reliability, transactions are executed based on the buy recommendations made by research houses registered with Bursa Malaysia. The weak form efficiency was tested based on the profits from selling signals of 5 most popular technical analysis indicators; namely shooting star, MACD oscillator, relative strength index, momentum indicator and simple moving average. The sell signals were generated using ChartNexus, one of the most contemporary technical analysis software. This study examined 547 buy recommendations from the recent year of 2013, involving 213 counters listed on Bursa Malaysia. The preliminary results showed that around 64 percent of the recommendations are accurate, i.e., generate positive returns. While the finding implies about 34 percent room of errors in the professional security analysts’ recommendations, the economically and statistically significant abnormal returns generated through the technical trading strategies provide solid evidence against weak form efficiency of the Malaysian stock market.